Monitoring and Analyzing of the Attacks of the Football Team - Viktor Kostiukevych; Natalia Shchepotina; Tetiana Vozniuk (OVS LLC, 2020)
The article describes a methodological approach to monitoring and analyzing attacks of a highly qualified football team. The aim of the research is to develop a methodology for monitoring and analyzing attacks of highly qualified football teams, taking into account various models of the game tactics. Material and methodology. The competitive activity of the national football teams at the 2018 World Cup was studied. Research methodology: analysis and generalization of the literature sources, lesson observation, video analysis of competitive activities, methods of mathematical statistics. Results. A protocol for registration attacks of the football team has been developed. The estimated scale of penetrating attacks and playing off of standard positions of the football team is identified. A different correlation of positional and fast attacks of national football teams, which used different tactical models of the game, has been established. In one half: for the tactical model "A", positional attacks were 32.3±4.35 (61.8%), fast attacks - 20.0±1.78 (38.2%); for the tactical model "B" - positional attacks - 25.2±4.32 (52.7%), fast attacks - 22.6±4.32 (47.3%); for the tactical model "C" - positional attacks - 32.5±3.49 (67.7%), fast attacks - 15.5±3.96 (32.3%); for the tactical model "D" - positional attacks - 19.2±2.87 (41.9%), fast attacks - 26.6±2.87 (58.1%). At the 2018 world Cup, out of 169 goals, 111 (65.4%) were scored as a result of completing positional attacks, 35 (20.7%) - after playing off of the standard positions, and 23 (13.9%) - after implementing penalty kicks. Conclusions. Monitoring and analyzing the attacks of a football team allows managing persistently the competitive activities of football players both at the operational level during a single game and at the current level during a competitive tournament.